Respuesta :
We can rearrange the initial equation to y=mx+b
y=2x-5
Since perpendicular slopes must equal -1,
x=the perpendicular slope
2x=-1
x=-1/2
(Or you can just take the negative reciprocal above is just the "formula form" for it)
Therefore, the perpendicular slope is -1/2
y=2x-5
Since perpendicular slopes must equal -1,
x=the perpendicular slope
2x=-1
x=-1/2
(Or you can just take the negative reciprocal above is just the "formula form" for it)
Therefore, the perpendicular slope is -1/2
Make y the subject,
y - 2x = -5
y = 2x - 5
Now that y is the subject, the coefficient of x is your slope. HOWEVER! We are finding the slope perpendicular to this. Use the rule:
m1 * m2 = -1
Where m1 is the slope and m2 represents the perpendicular slope. Sub in 2 (from previous step)
2 * m2 = -1
m2 = -1/2
Therefore, your slope perpendicular to y - 2x = -5 is -1/2!
Hope this helped! Ask me if there's any part of the working you don't understand :)
y - 2x = -5
y = 2x - 5
Now that y is the subject, the coefficient of x is your slope. HOWEVER! We are finding the slope perpendicular to this. Use the rule:
m1 * m2 = -1
Where m1 is the slope and m2 represents the perpendicular slope. Sub in 2 (from previous step)
2 * m2 = -1
m2 = -1/2
Therefore, your slope perpendicular to y - 2x = -5 is -1/2!
Hope this helped! Ask me if there's any part of the working you don't understand :)